Complete characterization of ultrasound transducers through the "Field II" simulation program - GUIDI, G.; FLATERI, S. (Archives of Acoustics, 1999)
Acoustic field characterization is usually limited to the measurement of the field amplitude, and employs well-known investigation methods. However, it is known that in many applications an important role is played by the phase field distribution. For example, a complete acoustic field characterization (i.e. the determination of both the amplitude and phase field distributions), results very useful for the correct interpretation of the Doppler signals detected by such a transducer. In this paper a technique for the measurement of the complex field (phasor) produced by single element transducers is presented. It is based on the time domain analysis of the RF pressure signals produced in front of the transducer. The technique, proposed as a general experimental procedure for the concurrent measurement of phase and amplitude fields, is here applied to fields synthesized with the "Field II" simulation program. Simulation results are compared with field distributions both available in the literature in analytic form, or derived experimentally.